Methoprene-Tolerant (Met) Is Indispensable for Larval Metamorphosis and Female Reproduction in the Cotton Bollworm Helicoverpa armigera - Ma, Long; Zhang, Wanna; Liu, Chen; Chen, Lin; Xu, Yang; Xiao, Haijun; Liang, Gemei (Frontiers in Physiology, 2018)
Juvenile hormone (JH) represses larval metamorphosis and induces adult reproduction in insect. Methoprene-tolerant (Met) is identified as an intra-nuclear receptor medicating JH actions. In this study, we characterized a Met from the severe agricultural pest, Helicoverpa armigera (HaMet). In larval stage, HaMet is predominately expressed in the epidermis and midgut, and is up-regulated before each molting, whereas in adults HaMet is maximally expressed in the ovary, testis and fat body. Immunofluorescence observation revealed that HaMet was distributed in the longitudinal and circular muscle layers of midgut in larvae, whereas in the ovary of female adults, HaMet was detected in the oolemma and was localized in the cell nucleus. Knockdown of HaMet in last instar larvae led to the shortened time of pupation, the abnormal pupation, and the declined pupation rate. In female adults, depletion of HaMet severely suppressed the transcription of Vitellogenin (Vg) and Vitellogenin receptor (VgR), disrupted the Vg accumulation in fat body and the yolk protein uptake in oocyte, and finally led to an impaired fecundity. Our data therefore confirmed that HaMet acted as a nuclear receptor of JH, and played an essential role in larval metamorphosis and in female vitellogenesis and oocyte maturation.